Patented of Beverage Can Crusher Machines: Design Overview - Elfasakhany, Ashraf (Asian Review of Mechanical Engineering, 2020)
Recycling of Cans, beverage Cans, has rapidly increased in last decade; over recent years, the recycling of beverage Cans showed much more increasing as garbage disposal become great problem as well as recycling become economically feasible. One important need to support/help the increase of Can recycling processes is to develop the compulsory technologies for the crusher devices/machines. The aim of the current study is to present an overview of different designs for patents of the Can crusher machines. Such overview designs are believed to be useful for all inventors who worked on developing contemporaneous patents for the Can crusher machines.